Vermicomposting of cow dung amended with eggshell powder: Possible roles of eggshell powder on the growth models of Serendipita indica, wheat growth and performances and soil enzymes activity - Mohammad Zarea; Nasrin Karimi (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Chicken eggshell as a byproduct of the egg product industry makes serious problems to the environment. The aim of this study was to evaluate the effect of eggshell as a potential option in supplementing of the organic matter and improvement of soil conditions in the pot culture and the area. Method Two pot experiments were carried out to estimate the effects of CD and CDES vermicomposts provided from cow dung and cow dung + eggshell’s powder, respectively, on symbiotic relationships of Serendipita indica with wheat and soil enzyme activities tested under sterilized and non-sterilized soil conditions, respectively. Two in vitro experiments were also conducted to test the effects of eggshell extract and humic and fulvic acids extracted from CD vermicompost on S. indica growth.Results CDES vermicompost improved soil enzyme activities of urease, phosphatase and invertase. Root colonization of wheat with multiple species of mycorrhiza and facultative symbiont S. indica was improved by CDES. S. indica growth was induced by eggshell extract. Humic and fulvic acids increased in S. indica mycelia mats dry yield. Results revealed when cow dung was amended with eggshell powder provided a better condition for earthworm growth and enhancing the colonization percentage of wheat root with indigenous mycorrhizal fungi. CDES vermicompost caused the increase in soil basal respiration and soil enzymatic activities.Conclusion Eggshell powder growth promoting effect can be attributed to the biologically active compound that exists in eggshell extract.